Peran Guru Dalam Membentuk Akhlakul Karimah Peserta Didik di Madrasah Ibtidaiyah El Fajr Palembang - Bagus Setiawan; Ria Astina; Cindi Pramita (IBTIDAIYAH: Jurnal Penelitian dan Pendidikan Dasar Islam, 2026)
The decline in moral behavior among elementary school students is a serious challenge in the world of education, especially in the madrasa environment. Differences in family background, the influence of the social environment, and the development of digital technology also influence students' attitudes and behavior at school. This condition demands an optimal role for teachers in shaping and fostering moral behavior in students. This study aims to describe the role of elementary school teachers in shaping moral behavior among students at the El Fajr Palembang Elementary Madrasah. This study uses a qualitative approach with a descriptive research type. The research subjects include class teachers and students. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers play a role in shaping moral behavior through role models, habituating religious behavior, integrating moral values ​​into the learning process, and ongoing guidance.